Establishing energy-efficient retrofitting strategies in rural housing in China: A systematic review - Congxiang Tian; Nur Azfahani Ahmad; An Nisha Nur Welliana Abd Rased; Suqi Wang; Haining Tian (Results in Engineering)
This study investigates the urgent need for energy-efficient retrofitting in rural residential buildings across China, where older construction methods compromise energy performance and sustainability. Conducting a systematic review of studies from 2021 to 2023, the research examines current retrofitting practices. It identifies significant gaps in the adoption of sustainable materials, passive design elements, and their local adaptability. This review period reflects heightened policy initiatives under China's Dual-Carbon Goals, aiming to peak carbon emissions by 2030 and achieve carbon neutrality by 2060, which accelerated efforts in sustainable retrofitting across rural areas. Key findings indicate a gradual adoption of advanced retrofitting methods, yet significant obstacles remain, such as financial limitations, insufficient policy support, and lack of technical expertise. A closer examination highlights innovations like advanced insulation materials, photovoltaic systems, and simulation models as dual-benefit tools for energy efficiency and cultural preservation. Despite advancements, integrating policy support frameworks, financial incentives, and community-based strategies are crucial to overcoming existing barriers. This study emphasizes the importance of culturally adaptive retrofitting solutions tailored to rural contexts, suggesting that these strategies are essential to encourage wider acceptance and long-term sustainability. Ultimately, this review provides a comprehensive overview of effective retrofitting practices and underscores the need for holistic policy mechanisms and economic models to advance China's sustainability objectives in rural housing.